Climate change, uncertainty and allostatic load - D. E. Crews; N. C. Kawa; J. H. Cohen; G. L. Ulmer; A. N. Edes (Taylor & Francis Group, 2019)
Context: Humans constantly respond to environmental stressors challenging their somatic stability. Allostasis, an evolved neuroendocrine/physiological stressor response system, is our main pathway for doing so. Effective allostasis returns somatic systems to their current optima; over a lifetime of stressor responses, related systems fail, effectiveness declines, and physiological dysregulation (i.e. allostatic load) increases. Global Climate Change (GCC) multiplies environmental stressors on human populations and is likely to increase allostatic load. Objectives: As a population-level stressor, GCC increases risks for multiple stressors, including sociocultural instability and food and water insecurity, while also motivating migration. We predict GCC increases risk for elevated allostatic load. Here, we review pathways by which GCC increases climatic and social stressors contributing to greater stress and allostatic load. Methods: Based upon published sources and primary ethnographic case studies, this review examines how GCC, by multiplying climate-related stressors, likely increases social instability, food and water insecurity, and migration. Thereby, it is proposed that GCC contributes to allostatic load. Results: GCC multiplies stressors on local populations. Those experiencing social insecurity related to GCC during growth and development are expected to show the largest influences on their lifetime allostatic load. Similarly, as GCC increases food and water insecurity, it likely will increase allostatic load in those affected and is likely to propel migrants to seek improved living circumstances. These stressors may be continued among their descendants via historical trauma or epigenetic responses. Conclusion: GCC accentuates effects of environmental and sociocultural stressors on human populations. Those exposed to GCC are likely to show lifelong elevated allostatic load.